Investigating the impact of service climate on intention to revisit a hotel: the mediating role of perceived service quality and relationship quality. Issue 1 (2nd January 2017) - Sadeghi, Mohsen; Zandieh, Dina; Mohammadi, Mahmoud; Yaghoubibijarboneh, Bahram; Nasrolahi Vosta, Simin
Abstract: The purpose of this paper was to examine the effect of service climate on the intention to revisit a hotel in terms of the role of service climate and relationship quality (satisfaction and trust). In fact, the effect of service climate and relationship quality on the relationship between service climate and revisit intention would be addressed. The model was tested in an empirical study with data from a survey of 200 hotel employees and 200 guests of three-, four-, and five-star hotels in the area of Tehran. Data were collected by two questionnaires using a convenience sampling approach. The research model was then tested by path analysis with LISREL ™ software. Results indicated that there is a positive and significant relationship between service climate and intention to revisit. Further, perceived service quality and relationship quality were mediating variables in the relationship of service climate and revisit intention. The research provides valuable insights into the role of service climate in the hotel service experience. Service climate makes a signiﬁcant contribution to the prediction of behavioural intentions (such as satisfaction, trust, and revisit intention).